Range of Types of Local Element Synthesis Forms and Non-Local on Villa Isola Building in Bandung City - Dwiyandana, Dani (Ann Publisher, 2023)
The Indis architecture of the 1920s to 1940s in Indonesia was a phenomenon of the formation of Dutch colonial buildings with high architectural value that still survive today. The shape results from combining modern European architecture with Indonesian vernacular architecture. The research uses a range theory approach to the type of architectural synthesis forms, architectural synthesis theory, local and non-local elements theory, architectural synthesis form theory, archetypes theory, and typology theory. The research methodology is carried out with qualitative and quantitative approaches. The qualitative approach is descriptive and interpretative research, where the data is more concerned with interpreting local and non-local architectural elements in the object of study. The quantitative approach is confirmatory to prove it under the research objectives. The results of the study are expected to provide an understanding of the range of types of synthesis forms of local and non-local elements; aspects that affect the range of types of synthesis forms; form, form, and type of architectural synthesis; the range type model of the architectural form on Indis architecture building.